Management of Post Harvest Diseases of Fruits using Plant Products - Kumari, Neelam; Singh, Deepika; Thakur, Ashok K. (International Journal of Economic Plants, 2016)
This review deals with the scope of using some botanicals for the management of post harvest diseases of fruits, thereby prolonging their shelf life. Plant products are an important source of agrochemicals used for the control of various post harvest losses including diseases as well as insect pests. The overzealous and indiscriminate use of most of the synthetic fungicides has created different types of environmental and toxicological problems. Recently, in different parts of the world, attention has been paid towards exploitation of higher plant products as novel chemotherapeutants in plant protection. These are being used to manufacture natural or biopesticides, which are environmental friendly and do not have any toxic effects on plants and soil.